Association between systemic inflammatory response index and glaucoma incidence from 2005 to 2008 - Li, Xiang; Sun, Yi Qing; Zhong, Xiao Dan; Zhang, Zhi Jie; Tang, Jia Feng; Luo, Zhan Yang (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the association between the Systemic Inflammatory Response Index (SIRI) and glaucoma using data from the 2005–2008 National Health and Nutrition Examination Survey (NHANES).MethodsWe performed a cross-sectional analysis using data from NHANES (2005–2008). Among participants who underwent non-mydriatic retinal imaging and Frequency Doubling Technology (FDT) visual field testing, 4,514 were included after excluding those with missing key variable data. SIRI and other inflammatory indices, including the systemic immune-inflammation index (SII), platelet-to-lymphocyte ratio (PLR), and neutrophil-to-lymphocyte ratio (NLR), were calculated from blood samples. Logistic regression models were employed to assess the relationship between these indices and glaucoma, adjusting for demographic and health-related variables.ResultsA significant positive association was found between elevated log2SIRI levels and the prevalence of glaucoma (Model 3: OR 1.24, 95% CI 1.07–1.44, p < 0.005). We performed an in-depth analysis of the Log2SIRI quartiles and found a significant association between Log2SIRI Q4 and the occurrence of glaucoma (Model 3: OR1.62, 95%CI 1.12–2.34, p = 0.011). This correlation was further validated using the area under the receiver operator characteristic curve (AUC) in Model 3(AUC = 0.674).ConclusionElevated SIRI levels are significantly associated with the prevalence of glaucoma, highlighting the potential role of systemic inflammation in glaucoma pathogenesis. SIRI may serve as a useful biomarker for identifying individuals at risk of glaucoma, facilitating early detection and targeted intervention strategies. Further research is needed to validate these findings and explore their clinical applications.